Changes in the sexual experience and awareness of social sciences students during a decade in Eastern Turkey - Özdemir, Enver; Aygen, Murat (EuroJournals, Inc., 2011)
We investigated and analyzed the change in the status of sexual experience and awareness of the Social Sciences Faculty students in ten years. The study was conducted in two stages each comprising 245 Social Sciences Faculty students first in 2000-2001 and the second in 2009-2010 educational years. Significantly more students confessed sexual experience (from 45.3% to 59.6%), and this was trebled among female ones over a decade (from 16.8% to 51.2%). While the age at the first sexual experience was become elder significantly, confession of first sexual experience under 20 years old among female students was increased from 5.6% to 23.2% over a decade. Although, sexual experience with a first time seen partner was dropped from 17.6% to 14.3%, the number of foreign sexual partner was trebled. The increase in the percentage of the students confessing sexual experience, risky sexual behaviours and lack of awareness may suggest the obvious need for starting formal sexual education. © EuroJournals Publishing, Inc. 2011.
Keywords: Adolescents; Behavior; Education; Public health; Sexuality